Transformation Of The Mindset And Entrepreneurial Skills Of Polytechnic Students Through A Project-Based Learning Approach - Usman, Hapsa; Tuati, Nonce Farida; Manuain, Deetje W. (Politeknik Negeri Ambon, 2025)
Entrepreneurship learning from an early age is needed to improve the progress of a country. The presence of entrepreneur groups can create jobs, increase welfare and per capita income, and reduce unemployment. This research aims to find ways to improve entrepreneurial mindset and entrepreneurial skills through project-based entrepreneurship learning. The method used in this study is an action research with a project-based learning (PJBL) approach applied to 2nd semester students of the public sector accounting study program with 80 students divided into 16 groups as informants. The findings in this study show that PJBL produces product development outputs from each student group team formed and in accordance with the Minimum Completeness Criteria (KKM). Therefore, PJBL plays an important role in improving students' entrepreneurial mindset and entrepreneurial skills in honing their knowledge and skills to become entrepreneurs. Keywords: entrepreneurial mindset; entrepreneurial skill, project-based learning.